(untitled) (Research, Society and Development, 2023)
Objective: Building an Investigative Teaching Sequence (ITS), which involves different pedagogical strategies for the development of student protagonism with the theme: animal biodiversity. Methodology: this study is categorized as a field research in a rural area, and also a participanting observation. Twenty students from the third year of public high school participated in this educational action, divided into four teams, totaling six class hours. Four stages were part of this experience. STAGE 1: problematization of the generating theme (How is the fauna of my locality presented itself?) and field class with Local Faunistic Survey (LFS); STEP 2: description from at least three synapomorphic characteristics of vertebrate groups identified in the LFS; STAGE 3: theoretical discussion about the content, construction of food webs, categories of the biotic environment and trophic levels from the LFS; STAGE 4: introducing of the materials produced and confrontation of ideas. Results: The teams identified 184 animals, distributed in 29 species; 06 classes, 03 of which are vertebrates. It was discussed the biological concepts such as richness and abundance. Teams II and IV nicely reached all stages. However, only two synapomorphic characteristics were described and error in the identification of trophic levels in teams I and III, respectively. Conclusion: ITS, when well planned, sharpens the construction of new knowledge, stimulates students’ intellectual freedom, develops argumentation, as well as critical reflection, scientific reasoning, which are basic assumptions for Teaching Biology by Investigation.